Construction of laccase based electrochemical biosensors for detection of clonazepam (2024)
Pharmaceutical industry waste and wastewater are becoming a very huge pollution problem more and more, not only because of the lack of water treatment methods but also by the incontrollable arrival of drugs at natural water reservoirs. Voltammetry is one of the quantification techniques used to detect those drugs. Using a potentiostate and electrochemical electrodes it is possible to quantify pharmaceutical particles in the water. Additionally, the electrodes can be functionalized to enhance their performance using enzymes acting as redox reactions catalyzers augmenting the speed of Clonazepam electrons release at 0.611V with the best sensor made. This study details the process of five Laccase based Biosensors fabrication to quantify Clonazepam in water using redox reactions, finding that is possible to fabricate sensors easily and with high reproducibility to ap-proximate the concentration of the drug dissolved with very low error.